2008 IEEE International Electron Devices Meeting 2008
DOI: 10.1109/iedm.2008.4796679
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of magnetic tunnel junctions for high-density spin torque transfer-MRAM (STT-MRAM)

Abstract: We have demonstrated a robust magnetic tunnel junction (MTJ) with a resistance-area product RA=8 Ω−µm 2 that simultaneously satisfies the statistical requirements of high tunneling magnetoresistance TMR > 15σ(R p ), write threshold spread σ(Vw)/ <7.1%, breakdown-to-write voltage margin over 0.5V, readinduced disturbance rate below 10 -9 , and sufficient write endurance, and is free of unwanted write-induced magnetic reversal. The statistics suggest that a 64Mb chip at the 90-nm node is feasible. Introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…In conclusion, we summarize the potential benefits of the proposed TMA MRAM and compare it with the conventional STT MRAM with PMA in terms of crucial memory design attributes (see Table 1). The ratio of the read current density (while reading data "zero") to the critical switching current density corresponding to the write frequency same as the read frequency has been designated as (J READ /J DISTURB ) [34], [35].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we summarize the potential benefits of the proposed TMA MRAM and compare it with the conventional STT MRAM with PMA in terms of crucial memory design attributes (see Table 1). The ratio of the read current density (while reading data "zero") to the critical switching current density corresponding to the write frequency same as the read frequency has been designated as (J READ /J DISTURB ) [34], [35].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 2a, the group with a length of 20 nm showed the best performance with a current density of 1 MA/cm 2 and an I on /I off ratio of $10 4 , which is acceptable for an STT-MRAM [4]. Moreover, after adjusting the slope of the doping profile in the Si 0.8 Ge 0.2 and Si interface, it was found that a steeper slope gives better performance, as shown in Fig.…”
Section: Introductionmentioning
confidence: 90%
“…Essential characteristics of a selective device include simple structure and high performance. In an STT-MRAM, a bidirectional current flow and high current drivability of more than 10 6 A/cm 2 should be achieved for device operation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we will not attempt to provide a global view, but will focus on three recent projects from our nanomagnetics group at Cornell University, Ithaca, New York: (i) progress in reducing the critical current for spin-transfer-driven magnetic switching [5], (ii) measurements of the bias dependence of the spin torque in magnetic tunnel junctions using spin-torque-driven ferromagnetic resonance (ST-FMR) [6], and (iii) single-shot measurements of the magnetic dynamics during the process of spin-torque switching [7]. [8][9][10][11]. The primary remaining challenges for commercialization of this technology are to minimize the current required for switching while maintaining sufficient thermal stability for the memory devices and while maximizing the switching speed, demonstrating that the magnetic tunnel junctions used as memory elements can withstand the relatively large current densities needed for spintorque switching without damage during extended use, and demonstrating sufficient reproducibility in the switching characteristics of the magnetic elements.…”
Section: Introductionmentioning
confidence: 99%